Agile leadership among the leaders of public primary schools in Unayzah Governorate from the point of view of the teachers - Al-Towaijri, Hailah Mandeel; Al-Buraikan, Sohad Abdulrahman; Al-Khalifah, Hind Khalifah; Al-Romaihi, Maram Rumaih (Journal of Educational and Psychological Sciences, 2023)
The research aims to identify the degree of agile leadership style application by public primary schools’ leaders in Unaizah Governorate from teachers point of view, in the light of the two variables (years of experience and qualification). The research adopted the descriptive quantitative approach and a as a study tool consisted of a questionnaire of (25) items, data were collected from (250) female teachers who represent the research community. The study finding shows a high level of application of agile leadership characteristics of school principals as perceived by teachers at Unaizah governorate obtained a total level of (3.41 out of 5), where humility ranked at the highest level with average (3.69), calmness with average of (3.64), wisdom with an average of (3.62), objectivity with an average of (3.60), confidence with an average of (2.98), and patience with an average of (2.91). The results showed that there are differences in the estimates of teachers attributed to experience for those less than 5 years of experience, while there are no differences according to education. In the light of the study findings, researchers suggests provide more necessary training for school leaders, providing clear criteria for the requirements of agile leadership, and periodic evaluation of the availability of agile leadership requirements in educational institutions. And motivating leaders to develop their skills and professional capabilities, in addition to making suggestions for complementary studies on the subject.